2016
DOI: 10.1021/acscatal.6b01636
|View full text |Cite
|
Sign up to set email alerts
|

A Biocatalytic Aza-Achmatowicz Reaction

Abstract: A catalytic, enzyme-initiated (aza-) Achmatowicz reaction is presented. The involvement of a robust vanadium-dependent peroxidase from Curvularia inaequalis allows the simple use of H2O2 and catalytic amounts of bromide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 22 publications
3
39
0
Order By: Relevance
“…First, we evaluated the influence of several reaction parameters, such as pH and reagent concentration, on the efficiency of the bromolactonization of 4‐pentenoic acid. In accordance with our previous findings, the reaction proceeded optimally at pH 5 (with more than 80 % activity at both pH 7 and pH 4; Table ). Although this behavior can most likely be attributed to the pH‐dependency of the biocatalyst, the protonation stage of the carboxylate group may also play a role here.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…First, we evaluated the influence of several reaction parameters, such as pH and reagent concentration, on the efficiency of the bromolactonization of 4‐pentenoic acid. In accordance with our previous findings, the reaction proceeded optimally at pH 5 (with more than 80 % activity at both pH 7 and pH 4; Table ). Although this behavior can most likely be attributed to the pH‐dependency of the biocatalyst, the protonation stage of the carboxylate group may also play a role here.…”
Section: Methodssupporting
confidence: 92%
“…In particular, the V‐dependent chloroperoxidase from Curvularia inaequalis ( Ci VCPO) is a very promising catalyst with exceptional activity and stability . Previously, we have applied this enzyme for the halogenation of phenols, hydroxyhalogenation of alkenes, and, inspired by the pioneering work by Deska and co‐workers, to mediate (aza‐)Achmatowicz reactions . In the current study, we investigated the suitability of Ci VCPO to initiate the spontaneous halolactonization of γ,δ‐unsaturated carboxylic acids (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…As starting point we chose the optimised reaction conditions determined previously. 13,14 Full conversion was achieved after 4 hours with high selectivity towards vic-bromohydrin (490%) with only trace amount of side products (epoxide, ketone derivatives) detectable (Table 1, entry 2). The regio chemistry of the hydroxybromination reaction exclusively followed Markovnikov's rule.…”
mentioning
confidence: 99%
“…Unfortunately, many biological buffers (Good's buffers) are amines and are thus not suitable for use with aminophenyl fluorescein in the HOX assay . For example, the 50 mM Tris‐H 2 SO 4 used in the standard Ci VCPO storage buffer significantly inhibited the HOX assay (2.5 mM Tris‐H 2 SO 4 in the final reactions). Desalting the Ci VCPO into phosphate buffer (50 mM, pH 8.0) using PD10 columns significantly increased the sensitivity of the assay.…”
Section: Resultsmentioning
confidence: 99%
“…The standard substrate used for initial screening of dehalogenase libraries is dibromoethane, making the detection of bromide very important . Initially, one of our reasons for considering the vanadium‐dependent chloroperoxidase from Curvularia inaequalis ( Ci VCPO) was its high activity in the presence of 50 nM bromide . This suggested that the Ci VCPO could be used for the detection of nanomolar concentrations of bromide, which turned out to be true (Figure , Table ).…”
Section: Resultsmentioning
confidence: 99%